2020
DOI: 10.1080/20477724.2020.1719701
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of fluoroquinolone-resistantSalmonellaserotypes in Iran: a meta-analysis

Abstract: The present study was conducted to investigate the antimicrobial susceptibility profiles of Salmonella serotypes, especially fluoroquinolone-resistant strains, recovered from clinical samples in Iran. A full electronic search using related keywords was conducted in Persian and English languages in ISI Web of Knowledge, PubMed, Scopus, Google Scholar and the Scientific Information Database (SID) search engines to find papers published between 1983 and 1 July 2019. According to the inclusion and exclusion criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
2
17
1
Order By: Relevance
“…This finding is in line with the current situation in Tehran, where no ciprofloxacin-resistant isolates were detected among 174 S. enterica strains (32). However, a comprehensive analysis by Khademi et al revealed that the pooled occurrence of ciprofloxacin-resistant Salmonella serotypes in clinical specimens was 2.9% in Iran (11). In Salmonella spp., point mutations at QRDR of DNA gyrAse are mainly the cause of quinolone resistance between amino acids 67 and 106, which can alter the binding site of the agents with DNA gyrAse (33).…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This finding is in line with the current situation in Tehran, where no ciprofloxacin-resistant isolates were detected among 174 S. enterica strains (32). However, a comprehensive analysis by Khademi et al revealed that the pooled occurrence of ciprofloxacin-resistant Salmonella serotypes in clinical specimens was 2.9% in Iran (11). In Salmonella spp., point mutations at QRDR of DNA gyrAse are mainly the cause of quinolone resistance between amino acids 67 and 106, which can alter the binding site of the agents with DNA gyrAse (33).…”
Section: Discussionsupporting
confidence: 71%
“…According to their results, the pooled prevalence of nalidixic acid-resistant isolates in Iran was 48.1%. Moreover, from 1983 to 2019, the nalidixic acid-resistance trend of Salmonella serotypes was increasing in Iran (11).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance of Salmonella isolates to fluoroquinolone like ciprofloxacin (2.27%) and third-generation cephalosporin (ceftriaxone 16.68%) were also reported. Similarly, according to Tadesse's report, the pooled prevalence of ciprofloxacin resistance among Salmonella isolates was 3.61% [80] and a prevalence of 2.9% of resistance against ciprofloxacin was also reported in Iran [81].…”
Section: Plos Onementioning
confidence: 87%
“…Although Salmonella infections are usually limited to uncomplicated diarrhoea, for the elderly or an immunocompromised person, they can cause severe infections, which may be life-threatening and may require an antimicrobial therapy. However, an increase in Salmonella strains resistant to antimicrobial agents commonly prescribed to treat salmonellosis has become a significant problem [2,3]. Fluoroquinolones (FQ) are first line drugs for treating serious Salmonella infections in adults.…”
Section: Introductionmentioning
confidence: 99%